Are Schools Alienating Digitally Engaged Students? Longitudinal Relations between Digital Engagement and School Engagement - Hietajärvi, Lauri; Lonka, Kirsti; Hakkarainen, Kai; Alho, Kimmo; Salmela-Aro, Katariina (Frontline Learning Research, 2020)
This article examined digital learning engagement as the out-of-school learning component that reflects informally emerging socio-digital participation. The gap hypothesis proposes that students who prefer learning with digital technologies outside of school are less engaged in traditional school. This hypothesis was approached from the framework of connected learning, referring to the process of connecting self-regulated and interest-driven learning across formal and informal contexts. We tested this hypothesis with longitudinal data. It was of interest how digital engagement, operationalized as a general digital learning preference, wish for digital schoolwork, and their interaction, is related to traditional school engagement. This was examined both cross-sectionally in three time points and longitudinally across three years. The participants were 1,705 (43.7% female) 7th–9th graders (13-15 years old) from 27 schools in Helsinki, Finland. We explored the structure of correlations between latent constructs at each time point separately, and finally, to evaluate longitudinal relations between digital engagement and school engagement we specified latent cross-lagged panel models. The results indicate that students holding a stronger general digital learning preference experienced higher schoolwork engagement, both contemporaneously and over time, indicating successful connected learning. However, the results also showed support for the gap hypothesis: Students who preferred digital learning but did not have the chance to digitally engage at school, experienced a decrease in school engagement over time. The article shows that there is a need to examine the reciprocal interactive processes between the learners and their social ecologies inside and outside school more closely.